2020
DOI: 10.2147/ppa.s176683
|View full text |Cite
|
Sign up to set email alerts
|

<p>Application of Once-Monthly Self-Reported ACT Questionnaire in Management of Adherence to Inhalers in Outpatients with Asthma</p>

Abstract: Poor medication adherence can negatively affect health outcomes of patients with asthma from medication and significantly increase the healthcare costs. Management of adherence to inhalers remains a challenging topic in the long-term management of patients with asthma. We aim to evaluate the role of asthma control test (ACT) in the management of adherence to inhalers in outpatients with asthma. Patients and Methods: Six hundred twenty-seven outpatients with asthma admitted to the clinic of respiratory medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…The results show that most of the responsibilities of hospital pharmacists in the patients' perceptions were fulfilled, while the patients' medication adherence was generally poor (Table 6). 16,17 Correlation Between Psychological…”
Section: Scores Of the Psychological Contract And The Medication Adhementioning
confidence: 99%
“…The results show that most of the responsibilities of hospital pharmacists in the patients' perceptions were fulfilled, while the patients' medication adherence was generally poor (Table 6). 16,17 Correlation Between Psychological…”
Section: Scores Of the Psychological Contract And The Medication Adhementioning
confidence: 99%
“…Indeed, in the first 6 months of therapy, a slight although not significant improvement in AE and ACT score was observed also in NR patients, but they showed no further improvement after 1 year of treatment. This suggests that the initial improvement was merely due to the increase in therapy compliance resulting from closer patient monitoring [ 33 ], rather than being an effect of the biological drug. Interestingly, the consequent switch to another biological drug offered to NR patients produced a significant and persistent decrease in AE already apparent after 1 year of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to ACT is very useful and very important beneficial for the management and control of asthma (Global Initiative for Asthma, 2020). The ACT questionnaire describes daily activity disturbances as a result of asthma, how often the patient complains of shortness of breath, whether there are symptoms at night, how often he uses spray/oral medication and how the level of asthma control is (Zhang et al, 2020). From previous studies, it was found that there is a relationship between the accuracy of using inhalers and whether or not asthma is controlled based on the ACT.…”
Section: Introductionmentioning
confidence: 99%